Repetitive magnetic stimuli over the motor cortex impair long-term consolidation of a balance task by suppressing up-regulation of intracortical inhibition - Sven Egger; Michael Wälchli; Samuel Meyer; Wolfgang Taube (Bern Open Publishing, 2024)
Introduction Recent findings have demonstrated that low-frequency repetitive magnetic stimulations (rTMS) over the primary motor cortex (M1) impaired short-term consolidation of a balance task, underscoring the causal connection between M1 and the consolidation of balancing skills (Egger et al., 2023). However, the underlying neural mechanisms induced by rTMS and whether these adaptations endure over an extended period, encompassing multiple acquisition sessions, remain insufficiently elucidated (Censor & Cohen, 2011). So far, its is widely acknowledged that GABAergic processes play an important role for consolidation (Sanes & Donoghue, 2000), at the same time, are affected by learning balance skills (Mouthon & Taube, 2019; Taube et al., 2020). Therefore, the present study aimed to investigate the impact of rTMS on GABA-mediated short-interval intracortical inhibition (SICI) and to explore the role of M1 in the long-term consolidation of a balance task (i.e., across multiple acquisition sessions). Methods Thirty-one volunteers underwent six balance acquisition sessions on a rocker-board, each followed by either rTMS or sham rTMS based on group affiliation. During the first and last training session, SICI was measured twice; before the balance acquisition and after the application of rTMS or sham-rTMS to investigate potential short- and long-term adaptations in intracortical inhibition. Adaptations were assessed during the execution of the learned balance task and in a non-learning postural control task (i.e., stable upright stance). Results Regardless of group affiliation, all participants achieved comparable improvements within the balance acquisition sessions. However, consolidation varied between groups. In particular, between the third and the fourth acquisition session, as Tukey corrected post-hoc tests showed a significant decline in performance for the rTMS group (p = 0.006). Both short- (p = 0.014) and long-term (p = 0.038) adaptations in SICI were affected by rTMS: while the sham rTMS group upregulated SICI, rTMS led to reduced levels of inhibition. No neurophysiological effects were observed in the non-learning control task (upright stance). Discussion/Conclusion The interfering effect of rTMS on balance consolidation and on upregulation of SICI indicates that increased intracortical inhibition is an important mechanism to protect and engrave newly acquired motor memory. Importantly, adaptations in SICI were only apparent during the execution of the learned task. References Censor, N., & Cohen, L. G. (2011). Using repetitive transcranial magnetic stimulation to study the underlying neural mechanisms of human motor learning and memory. The Journal of Physiology, 589(1), 21-28. https://doi.org/10.1113/jphysiol.2010.198077 Egger, S., Wälchli, M., Rüeger, E., & Taube, W. (2023). Short-term balance consolidation relies on the primary motor cortex: A rTMS study. Scientific Reports, 13, Article 5169. https://doi.org/10.1038/s41598-023-32065-x Mouthon, A., & Taube, W. (2019). Intracortical inhibition increases during postural task execution in response to balance training. Neuroscience, 401, 35-42. https://doi.org/10.1016/j.neuroscience.2019.01.007 Sanes, J. N., & Donoghue, J. P. (2000). Plasticity and primary motor cortex. Annual Review of Neuroscience, 23, 393-415. https://doi.org/10.1146/annurev.neuro.23.1.393 Taube, W., Gollhofer, A., & Lauber, B. (2020). Training-, muscle- and task-specific up- and downregulation of cortical inhibitory processes. The European Journal of Neuroscience, 51(6), 1428-1440. https://doi.org/10.1111/ejn.14538